Texas Abstract : New Painting in the Nineties - Colpitt, Frances; Pace, Linda; The McKinney Avenue Contemporary, Dallas (San Antonio : Art Pace - A Foundation for Contemporary Art, 1995)
Boccara, Laurent ; Griffin, Tad ; Lyon, Giles ; Mancuso, Joe ; Miller, Michael ; Parazette, Aaron ; Pomara, John ; Rosmarin, Susie ; Schwarz, Ludwig ; Tileston, Jackie ; Wallis, Shawn ; Wilcox, John
biografie, bibliografie
Texas Abstract : New Painting in the Nineties, Art Pace, San Antonio, Texas, 18 November - 22 December 1995 ; The McKinney Avenue Contemporary, Dallas, Texas, 5 January - 24 March 1996
Engels
boek